Sprint interval exercise versus continuous moderate intensity exercise: acute effects on tissue oxygenation, blood pressure and enjoyment in 18–30 year old inactive men - Kriel,Yuri; Askew,Christopher D.; Solomon,Colin (PeerJ, 2019)
Background Sprint interval training (SIT) can be as effective, or more effective, than continuous moderate intensity exercise (CMIE) for improving a primary risk factor for cardiometabolic disease, low cardiorespiratory fitness (CRF). However, there has been no direct comparison in inactive individuals, of the acute effects of a session of SIT with a work-matched session of CMIE on local oxygen utilisation, which is a primary stimulus for increasing CRF. Furthermore, post-exercise blood pressure (BP) and enjoyment, if symptomatic and low, respectively, have implications for safety and adherence to exercise and have not been compared between these specific conditions. It was hypothesised that in young inactive men, local oxygen utilisation would be higher, while post-exercise BP and enjoyment would be lower for SIT, when compared to CMIE. Methods A total of 11 inactive men (mean ± SD; age 23 ± 4 years) completed a maximal ramp-incremental exercise test followed by two experiment conditions: (1) SIT and (2) work-matched CMIE on a cycle ergometer on separate days. Deoxygenated haemoglobin (∆HHb) in the pre-frontal cortex (FH), gastrocnemius (GN), left vastus lateralis (LVL) and the right vastus lateralis (RVL) muscles, systemic oxygen utilisation (VO2), systolic (SBP) and diastolic (DBP) blood pressure and physical activity enjoyment scale (PACES) were measured during the experiment conditions. Results During SIT, compared to CMIE, ∆HHb in FH (p = 0.016) and GN (p = 0.001) was higher, while PACES (p = 0.032) and DBP (p = 0.043) were lower. No differences in SBP and ∆HHb in LVL and RVL were found between conditions. Conclusions In young inactive men, higher levels of physiological stress occurred during SIT, which potentially contributed to lower levels of post-exercise DBP and enjoyment, when compared to CMIE.
Keywords: HIIT; SIT; CMIE; NIRS; Blood pressure; Enjoyment; Sprint interval training; Continuous moderate intensity exercise; Inactive